Maternal serum preptin levels in the pathogenesis and diagnosis of gestational diabetes mellitus - Kıraç Utku, İrem; Demir, Esra; Özkan, Hanişe; Sahtiyancı, Berrak; Uzun, Hafize; Ekinci, İskender; Büyükkaba, Mitat; Durmuş, Sinem; Akarsu, Murat; Gelisgen, Remise; Tabak, Ömür (Society of Medical Biochemists of Serbia, 2023)
Background: Gestational diabetes mellitus (GDM) is a metabolic disorder that occurs during pregnancy that increases both maternal and fetal mortality and morbidity. It was investigated whether there is a change in circulating levels of preptin, a new peptide secreted from pancreatic beta cells, due to GDM in pregnant women. The relationship between serum preptin levels with insulin and other metabolic parameters was also evaluated in these subjects. Methods: Eighty-five patients diagnosed as GDM and 89 healthy pregnant women with 75 mg oral glucose tolerance test (OGTT) was assessed in terms of serum preptin levels. Results: The serum preptin levels of the GDM group were significantly higher than those of the control group (p=0.001; p < 0.01). For the cut-off value of preptin measurement of 335.3 ng/L, the sensitivity was 97.65%, specificity was 87.64%, positive predictive value was 88.3% and negative predictive value was 97.5%. The risk of developing the disease is 294.273 times higher in patients with preptin level of 335.3 and above. Conclusions: We think that the reason for the increase in serum preptin levels in GDM is probably the response to glucose. The current results indicate that preptin plays an important role in elucidating the pathology of GDM. In addition, the search for a practical marker for the diagnosis of GDM suggests that the measurement of preptin level is promising.

Uvod: Gestacijski dijabetes melitus (GDM) je metaboli~ki poreme}aj koji se javlja tokom trudno}e i pove}ava smrtnost i morbiditet i majke i fetusa. Ispitivano je da li po stoji promena u cirkuli{u}im nivoima preptina, novog peptida izlu~enog iz beta }elija pankreasa, usled GDM kod trudnica. Odnos izme|u nivoa preptina u serumu sa insulinom i drugih metaboli~kih parametara je tako|e procenjen kod ovih ispitanika. Metode: Osamdeset pet pacijenata sa dijagnozom GDM i 89 zdravih trudnica sa 75 mg oralnim testom tolerancije glukoze (OGTT) je procenjeno u smislu nivoa preptina u serumu. Rezultati: Nivoi preptina u serumu GDM grupe bili su zna~ajno vi{i od onih u kontrolnoj grupi (p=0,001; p < 0,01). Za grani~nu vrednost merenja preptina od 335,3 ng/L, osetljivost je bila 97,65%, specifi~nost je bila 87,64%, pozitivna prediktivna vrednost je bila 88,3% i ne - gativna prediktivna vrednost je bila 97,5%. Rizik od razvoja bolesti je 294.273 puta ve}i kod pacijenata sa nivoom preptina od 335,3 i vi{e. Zaklju~ak: Smatramo da je razlog za pove}anje nivoa serumskog preptina u GDM verovatno odgovor na glukozu. Sada{nji rezultati pokazuju da preptin igra va`nu ulogu u rasvetljavanju patologije GDM. Pored toga, potraga za prakti~nim markerom za dijagnozu GDM-a sugeri{e da je merenje nivoa preptina obe}avaju}e.
Nıvoı preptına u serumu majke u patogenezı ı dıjagnozı gestacıjskog dıjabetesa melıtusa
Keywords: Gestational Diabetes Mellitus; Insulin; Oral Glucose Tolerance Test; Preptin; Gestacijski Dijabetes Melitus; Oralni Test to Lerancije Glukoze; Preptin; Insulin